Membangun Potensi Peserta Didik Melalui Pembelajaran yang Aktif, Kreatif, dan Bermakna - Adin Tegar Cahya Pratama; Oktvia Arin Pertiwi; Disthanisa Laurent; Mutiara Cinta (Universitas PGRI Madiun, 2026)
One obstacle student face in understanding lessons is a learning process that lacks engagement and is tedious, thereby diminishing their interest, motivation, and active participation. Furthermore, many students remain passive, lacking the confidence to ask questions, give presentations, or express their opinions, even when they do not fully grasp the material being taught. Consequently, teachers need to foster a classroom atmosphere that is comfortable, enjoyable, and characterized by rapport, making it easier to guide and motivate students in their learning. This study aims to identify strategies teachers can employ to implement active, creative, effective, and enjoyable learning (PAKEM). A literature review method was used, involving the collection of relevant articles from Google Scholar. The findings indicate that such learning can be achieved through effective classroom management, the use of diverse learning media and resources, active student involvement, and the implementation of interactive teaching methods